Students from single-parent households: their issues & challenges - Syed Mahmood, Syarifah Rohaniah; Sangeetha, Naomi (2023)
Single parenthood has been predicted as one of the causes of poor academic performance among school students. Most studies in Western countries reported that children of single-mother and single-father families perform academically lower than children of two-parent families. A phenomenological method of inquiry and analysis was used to explain the challenges and issues faced by students from single-parent households. In-depth interviews were conducted with five secondary school students at Klang Valley. The findings revealed that the students experienced five types of challenges: lack of parental guidance, grief of losing a parent, conflict between divorced parents, financial constraint, and societal perception. In overcoming the challenges, five strategies, which are talking to someone, listening to music, expressive writing, becoming more independent and feeling grateful were employed.